Genetic Variability Among Isolates Of Xanthomonas Citri Subsp. Citri Based On Rep-Pcr (Applied Biological Research, 2014)
Citrus canker caused by Xanthomonas citri subsp. citri is one of the most  important disease of citrus in India. In the present study 23 isolates of  Xanthomonas citri subsp. citri were collected from Varanasi and Jaunpur  districts of Uttar Pradesh (India). Isolates showed similar biochemical  characteristics whereas molecular analysis involving repetitive polymerase  chain reaction [rep-PCR] (BOX-, ERIC- and REP-PCR) grouped these  isolates into six clusters at 50% similarity coefficient, thereby revealing  presence of variation in X. citri subsp. citri isolates.
Keywords: Canker; citrus; Xanthomonas; rep-PCR